Electric and Thermal Properties of a Single Phase Cable Buried in Soil: An Analysis with the Finite Element Method (FEM) - Kanikella Sushman Kumar (Institute of Advanced Engineering and Science, 2013)
Current carrying capacity of power cable should be determined by the maximum operating temperature which the insulation can withstand. The temperature rise in cable is mainly due to Joule’s loss in conductor and induced eddy loss in sheath. In this paper, based on the coupled electromagnetic-thermal theory, the power losses calculated in electric field analysis are used as the input data of thermal analysis to predict the temperature rise in different layers of cable. The Distribution radial temperature characteristic analyzed with the method of finite element. Result obtained indicates that the radial temperature distribution of the Single Phase cable do not flattened distribution. It is showed that the highest distribution radial temperature in the conductor shares, while the cable insulation near grounded showed lower distribution temperature as according to given boundary condition. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2086